Students' perception of their ideal teacher: influence of students' academic motivation - Chen, Kai Shen *; Sivasaranya Sivabathalingam, * (Sunway College Kuala Lumpur, 2015)
This study aims to examine whether students’ level of motivation to learn in a college influences how they perceive an ideal teacher. One hundred and twenty-two students participated in this study. Participants completed a questionnaire on their motivation and ideal teacher’s traits. Results support the view that students are generally extrinsically motivated. Students’ academic motivation corresponded to their perception of ideal teacher’s behaviour. This study recommends that teachers use different instructional strategies to motivate both intrinsic and extrinsic students.